Implementation of Problem-Based Learning Using Digital Posters on Advertisement Texts to Enhance Students' Writing Skills - Ulyani, Maya; Indah Dwi Jayanti, Widuri (Ahmad Dahlan Journal of English Studies, 2026)
Developing writing skills in vocational high schools remains a significant challenge, particularly in composing advertisement texts that require persuasive language, creativity, and audience awareness. Although student-centered and technology-integrated approaches are increasingly promoted, empirical studies examining the integration of Problem-Based Learning (PBL) with digital media in teaching advertisement texts are still limited. Addressing this gap, this study investigates the implementation of PBL supported by digital poster media to enhance students’ writing skills. This research employed a mixed-method approach using a one-group pre-test and post-test design. The participants were 36 tenth-grade students (aged 15–16) from the Visual Communication Design program at SMKN 5 Yogyakarta. Data were collected through classroom observations, interviews, documentation, and writing assessments, and analyzed using thematic analysis and descriptive statistics. The findings indicate that the implementation of PBL encouraged more active and contextual learning, as students engaged in collaborative problem-solving tasks to develop advertisement texts in digital poster form. Quantitative results show improvement in students’ writing performance from pre-test to post-test, particularly in vocabulary use, grammatical accuracy, and text organization. Qualitative data further suggest increased participation, collaboration, and confidence during the learning process. Overall, the study suggests that integrating PBL with digital poster media may support the development of writing skills in vocational English education contexts.